2008
DOI: 10.1080/07357900801941852
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Signaling Induces B7-H1 Expression Through MAPK Pathways in Bladder Cancer Cells

Abstract: TLR4 (Toll-like receptor 4) and B7-H1, which were known to be restricted to immune cells in the past, were found to be aberrantly expressed in a majority of tumor cells, facilitating tumor evasion from immune surveillance. Our study demonstrated that activation of TLR4 signaling in bladder cancer cells up-regulated B7-H1 expression. Furthermore, this regulation was significantly attenuated by ERK or JNK inhibitor. Our results elucidated the molecule mechanism of regulation of B7-H1 expression through TLR4 sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
81
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 20 publications
8
81
0
Order By: Relevance
“…Corroborative to our results, ERK activation was recently noted to be important for IFN-g-induced B7-H1 expression in multiple myeloma and dermal fibroblast cells. Thus, our results underline the important role of the MEK/ERK pathway in influencing B7-H1 expression and show, for the first time, this mode of action in human DC, which is similar to previously described mechanisms of ERK-dependent regulation of B7-H1 in myeloma, dermal fibroblasts and bladder cancer cells [48][49][50].…”
Section: Discussionsupporting
confidence: 70%
“…Corroborative to our results, ERK activation was recently noted to be important for IFN-g-induced B7-H1 expression in multiple myeloma and dermal fibroblast cells. Thus, our results underline the important role of the MEK/ERK pathway in influencing B7-H1 expression and show, for the first time, this mode of action in human DC, which is similar to previously described mechanisms of ERK-dependent regulation of B7-H1 in myeloma, dermal fibroblasts and bladder cancer cells [48][49][50].…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, TLR4 activation by LPS up-regulated B7-H1 expression in a concentration and time dependent manner (Gong et al, 2013). Qian et al also demonstrated that MAPK pathway, especially ERK pathway was involved in LPS-induced B7-H1 expression in bladder cancer cells and inferred that blocking of B7-H1 or ERK pathway may be new targeted molecular strategies for bladder cancer (Qian et al, 2008). All these results implied the associations of TLR4 and B7-H1 with UBC-related immune escape.…”
Section: Introductionmentioning
confidence: 64%
“…Previous studies showed that MAPK pathway, especially ERK pathway was involved in LPS-induced B7-H1 expression in bladder cancer cells (Qian et al, 2008). By using specific inhibitors, we studied the effect of blocking ERK pathway on B7-H1 expression and CTLs killing against T24 cells.…”
Section: Discussionmentioning
confidence: 99%
“…TLR-4, which was the first described one among TLRs, whose expression was identified not only in immune cells, but also in many kinds of malignant cells (Qian et al, 2008). The role of TLR-4 in cancer seems discrepancy according to several previous studies.…”
Section: Discussionmentioning
confidence: 99%